Effect of MAPK Inhibition on the Differentiation of a Rhabdomyosarcoma Cell Line Combined With CRISPR/Cas9 Technology: An In Vitro Model of Human Muscle Diseases. Issue 10 (31st August 2018) - De Luna, Noemí; Suarez-Calvet, Xavier; Garicano, Maialen; Fernandez-Simon, Esther; Rojas-García, Ricardo; Diaz-Manera, Jordi; Querol, Luis; Illa, Isabel; Gallardo, Eduard
Abstract: The human rhabdomyosarcoma cell line TE671 has been used extensively to study different aspects of muscle biology. However, its ability to differentiate and form myotubes has not been explored. Here, we examined muscle differentiation when we specifically stopped proliferation of human TE671 (WT-TE671) cells by using 1, 4-diamino-2, 3-dicyano-1, 4-bis[2-aminophenylthio]butadiene (U0126), an MAPK inhibitor. Our data show that treated cells initiated fusion, and myotube formation and that expression levels of dysferlin and myogenin were increased, whereas those of pax7 were decreased. Treatment of WT-TE671 cells with vitamin D3 alone and cotreatment with U0126 also promoted dysferlin expression. In addition, we knocked out the DYSF gene, which is involved in muscle differentiation, using CRISPR/Cas9 technology in WT-TE671 cells (Dysf-KO TE671). No dysferlin expression was observed before and after U0126 treatment. Although myogenin expression was absent in vehicle-treated Dysf-KO TE671 cells, after addition of U0126, myogenin reached levels similar to WT-TE671. This widely available source of human cells appropriately treated with U0126 may represent a useful model to study human muscle physiology in vitro. This dysferlin-deficient cell line should allow the study of pathophysiological pathways involved in dysferlin-deficient muscle and constitute a tool for high-throughput screening of therapeutic compounds for patients with dysferlinopathy and other muscle diseases.